Tautomerizable styrenic copolymers confined in AAO templates - Giussi, Juan Martín (2013)
The aim of this work is to prepare new keto-enol tautomerizable polystyrene copolymer nanofibers, by infiltrating the polymer into nanoporous anodized aluminum oxide (AAO) nanocavities, and to examine the influence of confinement effects on the polymer properties of nanostructured polymers in comparison to the bulk. The interest of this work lies, on the one side, on the presence of tautomeric groups that could lead to discriminate against specific substrates and, therefore, could make them interesting in biomedicine. And, on the other hand, on the topographic characteristic of oriented nanofibrous structures that could be convenient for cell regeneration. In this work nanostructured keto-enol tautomerizable polystyrene copolymer nanofibers, i.e. Styreneco- 2-methyl-3-oxo-5-phenyl-4-pentenonitrile (St-co-MOP) of different chemical composition, have been prepared under soft infiltration conditions of the polymer into AAO templates. For all compositions, SEM images show stacked nanofibers reproducing the dimensions of AAO nanopores and Raman confocal spectroscopy of the samples, confirms the homogenous chemical distribution of nanofibers through all the length of AAO pores. The glass transition temperature values for St-co-MOP copolymer nanofibers inside AAO nanocavities determined by differential scanning calorimetry are higher than those corresponding to the bulk copolymers. From thermograms of nanofibers obtained by thermo gravimetric analysis (TGA), in an air atmosphere, the existence of two thermal peaks is observed, the second one probably caused by the presence of tautomeric forms in the copolymers. Moreover, the elastics moduli found for the bulk copolymers are consistent with their employment for building extracellular matrices. In summary, this study clearly demonstrates the feasibility of producing nanofibers from styrene-co-2-methyl-3-oxo-5-phenyl-4-pentenonitrile (St-co-MOP) tautomeric polymers with a high degree of homogeneity and appropriate thermal and mechanical properties. Furthermore, preliminary results for tautomeric copolymers do not show cytotoxic effects, indicating that the obtained nanostructured copolymer combines several relevant properties required for its future applications as a biomaterial for cell scaffolds.